THE INFLUENCE OF INSTITUTIONAL OWNERSHIP, INDEPENDENT COMMISSIONERS AND CAPITAL INTENSITY ON TAX AVOIDANCE - Nurhaliza, Henti; Sari, Intan Rahma (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The practice of tax avoidance has gained significant attention in the realm of corporate finance and accounting due to its potential implications for both firms and governments. Tax avoidance refers to the legal minimization of tax liabilities through strategic financial and operational decisions, often involving the utilization of various loopholes and incentives provided by the tax code. This study aims to analyze the determinants of tax avoidance, both from institutional ownership and independent commissioners which are also from capital intensity factors. The method used is quantitative method using secondary data. The population in this study are manufacturing companies in the basic consumer goods sector listed on the Indonesia Stock Exchange in 2017 - 2021. The samples used in this study were 24 companies with an observation period of 5 years in the 2017-2021 period and the number of financial reports sampled in this study amounted to 120. The analysis used is descriptive statistical analysis and panel data regression analysis. The analytical tool used in this research is analysis with the help of the E-views Version 12 program. The results of the research conducted show that simultaneously institutional ownership, independent commissioners and capital intensity affect tax avoidance. Partially, institutional ownership has no effect on tax avoidance, independent commissioners and capital intensity have an effect on tax avoidance.